Enhancing palliative care through university-community partnerships: a systematic review of models, impacts, and challenges - Alaka Chandak; Priyadarshini Bhalchandra Kulkarni (BMC Palliative Care)
Abstract Background University-community partnerships (UCPs) represent a transformative model for integrating student experiential learning with community-based palliative care. These partnerships enhance empathy, interdisciplinary collaboration, and service delivery, while addressing gaps in end-of-life care. Aim This systematic review evaluated the effectiveness of UCPs in palliative care, focusing on their impact on student learning, community outcomes, and innovative practices. Methods Following the PRISMA 2020 guidelines, a systematic search was conducted across PubMed, Scopus, Web of Science, and CINAHL databases for studies published between January 2014 and March 2024. This search yielded 206 unique citations. Nine studies were included after the full-text screening. Grey literature sources (e.g., reports and web-based articles) were screened but excluded due to insufficient methodological rigor, and thematic synthesis was conducted using NVivo, with two independent reviewers performing data extraction. The Risk of bias was assessed using the ROBIS (qualitative) and RoB 2 (quantitative) tools. Results Of the 206 records screened, nine studies (eight qualitative and one quantitative) met the inclusion criteria. The identified UCP models include transactional, transformational, and community-based participatory research (CBPR), with CBPR noted for contextual adaptability. UCPs contributed to improving student empathy, interprofessional learning, and community empowerment. Barriers include limited resources, cultural mismatches, and inconsistent stakeholder alignments. Innovations, such as telehealth and virtual learning, were also observed. Conclusion UCPs have strong potential to enhance palliative care education and delivery. Scaling these models requires sustainable funding, culturally responsive approaches, and policy integration. Future research must emphasize longitudinal designs and standardized evaluation structures.